การศึกษาการบริหารโครงการก่อสร้างภาครัฐช่วงก่อนการดำเนินงานก่อสร้างและแนวทางการเร่งรัด - กฤษดากร สมานุกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
Project management in a government construction project is complicated because there are many administration procedures needed to be performed by various organizations. For an effective project administration, there is a need to study each issue that arises in each procedure and to set up preventive and protective measures to eliminate the problems. The objectives of this research are: (1) to study the procedures in project administration of government construction, (2) to analyze the problems and obstacles that contribute to the delay in each procedure, (3) to understand the causes of delay in each procedure, and (4) to set the measures to expedite the processes. The administrative procedures in pre-construction phase can be summarized in 14 steps which are government policy, model scheme for budgeting, feasibility study, arrangement for annual economical forecast, council of ministers approval, budget plan, proposed act, parliament approval, budget allocation, design, bidding procedure, price approval, proprietary right, and construction. From interviews conducted, there are 66 causes of delay. The three major causes of delay are. (1) protesting against the government sector to construct in the area (53.33%), (2) establishing the budget in advance before the fiscal year causing inconsistencies in the budget and rushing the procurement process before the end of fiscal year (46.67%), and (3) changing the uses of budget by some authorities and having ready to construction drawing before budget approval. (40.00%), This research presents the findings of 27 guidelines for project expedition. By using the Index of Concurrence (IOC), the result indicates that 17 guidelines are in accordance while 10 guidelines are not in accordance. The two guidelines with maximum IOC scores are. (1) arranging the pre-qualification process for the feasibility study and (2) establishing a provision for the government sector to be able to terminate the contract, if the delay is more than 50%.